B cell activation and antibody production - Durmaz, Emel Ozturk (DERI ZUHREVI HASTALIKLAR DERNEGI, 2013)
Background and Design: The development and maturation of B lymphocytes ensue within the bone marrow independent of the antigen. While going through a complex maturation process within the bone marrow, these cells express surface antigen receptors and eventually achieve functional and phenotypic maturity. Mature naive B cells express IgM and IgD molecules as surface antigen receptors. After completion of the maturation process within the bone marrow, mature naive B cells migrate to peripheric lymphoid organs expecting to meet their specific antigen. Humoral immune response is initiated within the peripheric lymphoid organs when mature naive B cells meet their specific antigen. The antigen receptors of mature naive B cells may directly recognize and be activated with polysaccharide, lipid, glycolipid and nucleic acid antigens and with tiny soluble molecules. However, recognition of and activation by protein antigens requires CD4+ T cell help. The activation of B cell is a complex procedure consisting of sequential steps. For protein antigens these steps involve: 1. Recognition of antigens by B cells and intracellular signaling cascade 2. Antigen presentation by B cells to Th cells 3. B cell activation with the help of Th cells 4. B cell differentiation (development of antibody releasing effector B cells, heavy chain isotype/ class switching, affinity maturation, development of memory B cells) 5. Elimination of antigens by released antibodies 6. Homeostasis (termination of humoral immune response).
Keywords: Humoral immunity; humoral immune system; B lymphocyte; B cell; antibody